The effect of light curing units, curing time, and veneering materials on resin cement microhardness - Nurcan Ozakar Ilday; Yusuf Ziya Bayindir; Funda Bayindir; Aysel Gurpinar (Elsevier, 2013)
Background/purpose: Several factors may affects microhardness of resin cement under veneering materials. The aim of this study was to evaluate the effect of different veneering materials, light-curing units and curing times (20/3, 40/6) on the microhardness of dual-cured resin cement. Materials and methods: We pressed dual-cured resin cement specimens (Clearfil SA cement, 5 mm diameter, 1 mm thick) between two microscopic glass slides covered with transparent polystyrene matrix strips to remove excess material, then irradiated them through a ceramic disc and a composite disc (A2 Esthet X HD, Dentsply, Caulk) with three types of high-power light-curing units as follows: conventional halogen light (quartz tungsten halogen) for 20/40 s, light-emitting diodes for 20/40 s and xenon plasma arc for 3/6 s. The control group specimens were cured under two layer transparent polyester matrix strips (n = 5). After dry storage in the dark (24 h/37°C), we recorded specimens' Vickers microhardness numbers (50 gF load/15 s) and made three indentations on the bottom surface of each one. Data were analyzed using analysis of variance and post-hoc comparisons using Duncan's test and the Student t test with a significance level of 5%. Results: Analysis of variance revealed significant differences in microhardness resulting from the different curing units, veneering materials and polymerization times (P < 0.05). The light-emitting diode curing unit produced higher microhardness values compared to the conventional halogen light and plasma arc light sources (P < 0.05). Both veneering materials, ceramic, and composite resin, exhibited significantly lower microhardness values than those of the control group (P < 0.05). Extended polymerization time increased mean surface microhardness values of the resin cement specimens (P < 0.05). Conclusion: Light-curing units, curing time, and veneering materials are important factors for achieving adequate dual cure resin composite microhardness. High-intensity light and longer curing times resulted in the highest microhardness values.